Extraction of Tanshinones Rich Extract of Danshen (Salvia Miltiorrhiza Bunge) Root Using Adsorptive (Non-Ionic) Macroporous Resins - Trong Bien, Tran; Thi Linh Giang, Pham; Thai Ha Van, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 3DO - 10.25073/2588-1132/vnumps.4333, 2021)
Tanshinones are an important lipophilic, bioactive diterpenoid group of danshen roots with many pharmacological activities. In this study, tanshinones rich extract of danshen roots, a typically valuable product of danshen, was prepared through a two-step process of extraction and purification. In which, adsorptive (non-ionic) macroporous resins were exploited in the purification step to remove impurities and enrich tanshinones. The obtained refined extract was red brownish dry powder with the following characteristics: loss on drying of 4.04 ± 0.18%, tanshinone IIA and cryptotanshinone content of 10.55 ± 0.21% and 5.78 ± 0.64%, respectively (the results met the requirements of the Tanshinones monograph in The Chinese Pharmacopoeia 2015). The overall yield of the established extraction process was 2.21 ± 0.12%, calculated by the weight of dry  extract. Keywords: Tanshinones , danshen, macroporous resins, tanshinone IIA, cryptotanshinone. References [1] X. Yan, Overview of Modern Research on Danshen, G. Du, J. Zhang, Danshen (Salvia Miltiorrhiza) in Medicine, Springer, Germany, Vol. 2, 2014, pp. 3-17. [2] C. Y. Su, Q. L. Ming, K. Rahman, H. Ting, L. P. Qin, Salvia miltiorrhiza: Traditional Medicinal Uses, Chemistry, and Pharmacology, Chinese Journal of Natural Medicines, Vol. 13, No. 3, 2015, pp. 163-182, https://doi.org/10.1016/S1875-5364(15)30002-9. [3] Y. Cui, B. Bhandary, A. Marahatta, G. H. Lee, B. Li, D. S. Kim, S. W. Chae, H. R. Kim, H. J. Chae, Characterization of Salvia Miltiorrhiza Ethanol Extract as An Anti-osteoporotic Agent, BMC complementary and alternative medicine, Vol. 11, No. 1, 2011, pp. 120-131, https://doi.org/10.1186/1472-6882-11-120. [4] J. Li, H. A. Chase, Development of Adsorptive (Non-ionic) Macroporous Resins and Their Uses in The Purification of Pharmacologically-Active Natural Products From Plant Sources, Natural product reports, Vol. 27, No. 10, 2010, pp. 1493-1510, https://doi.org/10.1039/c0np00015a. [5] Tanshinones, The Chinese Pharmacopoeia, China, 2015, pp. 398-399. [6] G. Tian, T. Zhang, Y. Zhang, Y. Ito, Separation of Tanshinones From Salvia miltiorrhiza Bunge by Multidimensional Counter-Current Chromatography, Journal of Chromatography A, Vol. 945, No. 1-2, 2002, pp. 281-285, https://doi.org/10.1016/S0021-9673(01)01495-9. [7] D. Wu, X. Jiang, S. Wu, Direct Purification of Tanshinones From Salvia miltiorrhiza Bunge by High‐speed Counter‐current Chromatography Without Presaturation of The Two‐phase Solvent Mixture, Journal of Separation Science, Vol. 33, No. 1, 2010, pp. 67-73, https://doi.org/10.1002/jssc.200900491. [8] M. Liu, X. H. Xia, Study on The Chemical Stability of Tanshinone IIA, Zhong Yao Cai, Vol. 33, No. 4, 2010, pp. 606-609, PMID: 20845791 (In Chinese). [9] X. Bi, X. Liu, L. Di, Q. Zu, Improved Oral Bioavailability Using a Solid Self-Microemulsifying Drug Delivery System Containing a Multicomponent Mixture Extracted from Salvia miltiorrhiza, Molecules, Vol. 21, No. 456, 2016, pp. 1-15. https://doi.org/10.3390/molecules21040456.